Technical report: a study of rainfall pattern that affect flooding using fuzzy logic approach / Shahiratul Amalina Abd Karim, Nurul Hazirah Norhaizin and Nur Fazlina Ismail - Abd Karim, Shahiratul Amalina; Norhaizin, Nurul Hazirah; Ismail, Nur Fazlina (2016)
Flood is a natural disaster which is a major inauspicious event affecting from the earth's natural processes. In Malaysia, the northeastern states are frequently hit by flooding and one of the affected-areas is Kelantan. Hence, this study assesses in determining the rainfall patterns that affect flooding by using Mamdani fuzzy inference system by applying the model to the Kuala Krai, Kelantan. This study emphasized the volume of rainfall in December 2014 as it was the worst flood event for the past 100 years. Five inputs variables which are the volume of rainfall of five main stations in Kuala Krai were utilize to get an output variable which is the volume of rainfall for whole Kuala Krai. Trapezoidal membership functions were employed for each variables and the relationship between variable will be characterized by using 243 IF-THEN rules with AND connection. Subsequently, the acquired output values were verified with the actual flood event in December 2014. All implementation done by using MATLAB Software. Since the result corresponds to the actual flood incident in December 2014, thus, the efficiency of fuzzy logic model display satisfactory levels in interpreting flood situation based on volume of rainfall in Kelantan.